Śrīmahābhāba prakāśa - Kahnāi Khuṇṭiā (Śrī Harisaṅkīrttana granthamāḷā, 1981)
Critical edition of a verse work, based on the discourses by Chaitanya, Vaishnavite leader, on his realization of the divine presence of Krishna, Hindu deity